2021
DOI: 10.3390/educsci11080434
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Collaboration Challenges in Project-Based Learning: The Student’s Perspective

Abstract: Project-based learning has been explored in a variety of contexts and different phases of education. Several implementation challenges are associated with project-based learning. Among these challenges is ensuring collaboration between students enrolled in a project assignment. The purpose of this study was to present several practical insights on how to tackle collaboration challenges in project-based learning. The study is based on the qualitative analysis of 67 reflections reports submitted by students who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
8

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 58 publications
0
10
0
8
Order By: Relevance
“…It is in line with previous researcher that found experience mastery occurs when teachers view their performance as madrasa teachers to be successful. It is possible that PBL leads to a more positive educational experience among students, leading to an increase in the pedagogic competence of madrasah teachers (Hussein, 2021;Owens & Hite, 2020;Tambak et al, 2021;Untari et al, 2020). The other study also found there are positive associations found between PBL and student outcomes support the possibility of mastery experiences (Amin et al, 2020;Hussin et al, 2018;Sari et al, 2019).…”
Section: Discussionmentioning
confidence: 78%
“…It is in line with previous researcher that found experience mastery occurs when teachers view their performance as madrasa teachers to be successful. It is possible that PBL leads to a more positive educational experience among students, leading to an increase in the pedagogic competence of madrasah teachers (Hussein, 2021;Owens & Hite, 2020;Tambak et al, 2021;Untari et al, 2020). The other study also found there are positive associations found between PBL and student outcomes support the possibility of mastery experiences (Amin et al, 2020;Hussin et al, 2018;Sari et al, 2019).…”
Section: Discussionmentioning
confidence: 78%
“…More than a learning outcome, peer collaboration is a pedagogical strategy ( Hussein, 2021 ). In PBL, peer collaboration can facilitate students’ exchange of resources, ideas, experiences, and knowledge, and can promote student motivation and persistence ( Koh et al, 2010 ; Lou & Kim MacGregor, 2004 ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the quantitative responses, students found resolution issues challenging, which emerged in the online setting described especially in the present study, in contrast to the first cycle of this DBR study, which in the blended learning setting, where the subsequent application of knowledge and skills was perceived as the second easiest to agree with. Some studies have presented PjBL-related challenges, for example, the uncertainty of the project assignment (Hussein, 2021) and a less rigorous understanding of engineering Fundamentals (Mills & Treagust, 2003). In the case of a completely online environment, studying engineering skills without physical experience in the laboratory can negatively affect about the Resolution, which would favor the choice of a blended learning approach by combining FTF and online activities (Garrison, 2016, pp.…”
Section: Discussionmentioning
confidence: 99%